2017
DOI: 10.29244/j-siltrop.8.1.26-34
|View full text |Cite
|
Sign up to set email alerts
|

KEANEKARAGAMAN MAKROFAUNA TANAH PADA BERBAGAI TIPE TEGAKAN DI AREAL BEKAS TAMBANG SILIKA DI HOLCIM EDUCATIONAL FOREST, SUKABUMI, JAWA BARAT Soil Macrofauna Diversity on Various Types of Stands in Silicas’ Post-Mining Land in Holcim Educational Forest...

Abstract: Soil Macrofauna has a very important role in maintaining soil fertility through the decomposition of organic matter, nutrient distribution, increasing soil aeration and so on. The existence of soil macrofauna are very important in helping the process of rehabilitation of post-mining land because they contribute to the improvement of the physical, chemical, and biological properties of soil. The purposes of this study are to identify and quantify the diversity of soil macrofauna in various types of stands and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Data processing was conducted to analyse and identify the soil fauna biodiversity, such as species diversity index (H') [16], species richness index (DMg) [17], species evenness index (E) [18], and soil fauna abundance [19]. In other hand, we also conducted the statistical analysis by using R-Studio, included the Least Significant Difference (LSD) Test to investigate the disparities in soil fauna abundance across different elevations as well as the Pearson Correlation Test to analyse the relationship between soil fauna existence with environmental factor (edaphic and climatic factor).…”
Section: Discussionmentioning
confidence: 99%
“…Data processing was conducted to analyse and identify the soil fauna biodiversity, such as species diversity index (H') [16], species richness index (DMg) [17], species evenness index (E) [18], and soil fauna abundance [19]. In other hand, we also conducted the statistical analysis by using R-Studio, included the Least Significant Difference (LSD) Test to investigate the disparities in soil fauna abundance across different elevations as well as the Pearson Correlation Test to analyse the relationship between soil fauna existence with environmental factor (edaphic and climatic factor).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the age of the reclamation affects the microclimatic conditions and soil properties such as soil pH, soil temperature and humidity, and high organic matter content in the soil. The high canopy cover of a plant and abundant biomass and litter can stabilize the microclimatic conditions, so that the soil fauna found will be more numerous and varied [18].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in light intensity in the study plot have a moderate correlation to the abundance of soil fauna, where the higher the light intensity, the lower the abundance of soil fauna. This is due to the absence of vegetation that blocks direct light from hitting the land surface and impacts the death of soil fauna [25]. Light intensity at three different heights showed no different values (Table 7).…”
Section: Relationship Between Soil Fauna Abundance and Climatic Factorsmentioning
confidence: 96%
“…Abundance describes the large number of individuals occupying a particular location. Therefore, the abundance value of mesofauna and soil macrofauna used in this study refers to the number of individuals of a species found in a particular location [25].…”
Section: Analysis Of Soil Fauna Datamentioning
confidence: 99%